Capital cities and royal dwellings of late Hellenistic Sophene and Commagene - Blömer , Michael (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This article explores the political and cultural landscapes of the Hellenistic kingdoms of Sophene and Commagene, with a specific focus on their capital cities and royal residences. The kingdoms, although often overshadowed by larger Hellenistic realms, played a crucial role in the geopolitical dynamics of the Near East. By examining archaeological findings and historical records, this study highlights the development of urban centers and fortresses that served not only as seats of power but also as symbols of royal legitimacy and cultural identity. Key urban sites such as Arsamosata, Samosata, and Arsameia are discussed to illustrate how these cities facilitated the amalgamation of local and Hellenistic influences, reflecting the complex interplay between cultural integration and political sovereignty. The article also addresses the challenges in tracing the precise historical and architectural evolution of these sites due to sparse archaeological evidence. Through a detailed analysis of the available data, the study reconstructs the role these cities played in the broader context of Hellenistic urbanization and regional governance, offering insights into the strategies used by the rulers of Sophene and Commagene to manifest their authority and connect with their subjects.